The active learning method of the Automotive Mechatronics course learning impact on stability - (:unkn) unknown (My University, 2011)
Motronic education sets of Lucas Nuller Firm, visual education sets of automotive firms, animations, films and written documents were used in the research. Education sets were used by the education software and the software performed realtime simulation. The richness of the written documents helped the students to learn about other subjects on automotive and it was observed that their interest in them increased. The objective findings of the research showed the effect of Active Learning Method in success and remembering what was taught in the class where it was applied. This research was done in the first half of the academic year 2007-2008 with 29 third-year students of Mechatronics Section of Marmara University Technical Education Faculty. In the research, the students were given three tests: a pretest, post-test and reminding test. The questions of the tests were prepared according to the opinions of the experts. These tests were checked with Kolmogrof - Simitrow test and it was determined that their distributions were not normal. Non-parametric statistical methods were applied to the distributions that were not normal. The results were analyzed with SPSS 13.0 program, Wilcoxon Signed Ranks test. When the results were examined, it was found, as expected, that Automotive Mechatronics Education was given more efficiently and effectively with the Active Learning Method. The research was elaborated and applied based on similar studies in the same field. We hope that this research will be reference to similar researches in the same field.
Keywords: Active learning; Automative Mechatronics; Mechatronics technology